The Impact of Macroeconomic Indicators on Zakah Receipt during the Covid-19 Pandemic Era - Adilia Rahayu; Prayogo Prasojo Harto; Efri S. Bahri (Falah: Jurnal Ekonomi Syariah, 2021)
This study aims to determine the impact of macroeconomic indicators on Zakah receipt during the Covid-19 pandemic era. This research is associative with the quantitative approach. The research sample is five Zakah institutions obtained based on purposive sampling. Secondary data in the research was sourced from the official website of the relevant institution. The data Analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results found that inflation had a negative and significant effect on Zakah receipts during the Covid-19 pandemic, while money supply had a significant positive effect on Zakah receipts during the Covid-19 pandemic. On the other hand, gold prices and exchange rates had no significant effect on Zakah receipts during the Covid-19 pandemic. The results of this study contribute to enriching knowledge, especially regarding the macroeconomic impact on Zakah receipts during the Covid-19 pandemic.